Prenatal Diagnosis of Congenital Mesenchymal Hamartoma of Liver: A Case Report - Sreelakshmi Kodandapani; Muralidhar V. Pai; Vijay Kumar; Kanthilatha V. Pai (Case Reports in Obstetrics and Gynecology)
Hepatic mesenchymal hamartoma is a rare benign tumor. We present an unusual case of a fetal abdominal cyst, later diagnosed histopathologically to be mesenchymal hamartoma of liver. The organ of origin was indeterminate on both prenatal and postnatal ultrasounds. As there are no specific sonological findings, whenever a large multicystic fetal abdominal cyst is seen, mesenchymal hamartoma should be considered as a possibility.